PENYIMPANGAN ASAS AMAN DALAM PENDAFTARAN TANAH OLEH KEPALA KANTOR PERTANAHAN KOTA JAMBI - Wiwik Diah Lestari; Meta Indah Budhianti (Fakultas Hukum Universitas Trisakti, 2022)
Land registration by the National Land Agency is based on the ideals of being straightforward, secure, affordable, current, and open, as stated in Article 2 of Government Regulation Number 24 of 1997 Regarding Land Registration. Problem statement: How are deviations from the authority of the Jambi City Land Office Head who disregard the security principle in the implementation of land registration based on Article 2 Government Regulation No. 24 of 1997 handled? Decision Number 12/G/PTUN.JBI addresses these issues. Research technique: qualitative descriptive analysis using interviews and main and secondary data. The study's findings are as follows: 1). According to article 2 of the government regulation from 1997, there are violations of the principle of security in land registration when the head of the Jambi City Land Office issues certificates without being meticulous and complete, which leads to the creation of multiple certificates; 2). The Judge's Decision's contents are improper because they fail to consider the security principle in land registration as stated in Article 2 of Government Regulation No. 24 of 1997.